Pengembangan Model Evaluasi Formatis Materi IPA Kelas V dan VI di SDN Cibodas 6 Kota Tangerang - Magdalena, Ina; Nabila, Aida; Septi, Syafani Mayang (Lembaga Yasin AlSys, 2023)
The changing times that have occurred have led to various changes in the use of learning media. In the 21st century, the learning media used are also adapted to the criteria of today's children who are already literate with technology. Teachers can create interesting and effective learning designs used in teaching and learning activities. Of course by utilizing existing technology today. The use of technology can make learning more interesting, creative and innovative so that students can take part in learning activities in a comfortable and enjoyable way, especially in science lessons at SDN Cibodas 6 Kota Tangerang. The type of research used in this research is research and development. This research was carried out at SDN Cibodas 6 Kota Tangerang in grades V and VI in science subjects. The data collected is quantitative and qualitative data. The data was taken from the results of interviews, observations and collection of supporting documents as material for analysis and evaluation of the learning designs that have been implemented at SDN Cibodas 6 Kota Tangerang. Research results obtained from the implementation of virtual reality-based 3-dimensional (3o) media are able to increase student interest and learning outcomes to produce a good impact. This is indicated by the increase in student scores after implementing a 3-dimensional virtual model-based learning design which shows good results. The overall score is that there are many students who are under the KKM after the implementation of virtual media can reduce the scores of students who are under the KKM so that many students pass the subject matter. So it can be concluded that the application of learning models using 3D media has proven effective and can be adopted by other schools in increasing learning demand and student achievement at school.